170913 初版 170913 更新
\(\dfrac{dy}{dx}=\dfrac{dy}{du}\cdot\dfrac{du}{dx}\)
\(y=(f\circ g)(x)\), \(y=f(u)\), \(u=g(x)\) とします。
\(\Delta u = g(x+\Delta x)-g(x)\) とおきます。
\(\dfrac{(f\circ g)(x+\Delta x)-(f\circ g)(x)}{\Delta x}\)
\(=\dfrac{f(g(x)+\Delta u)-f(g(x))}{\Delta x}\)
\(=\dfrac{f(u+\Delta u)-f(u)}{\Delta u}\cdot
\dfrac{g(x+\Delta x)-g(x)}{\Delta x}\)
したがって,条件が整えば
\(\dfrac{dy}{dx}=\dfrac{dy}{du}\cdot\dfrac{du}{dx}\)
が成り立つことがいえました。
例 1
\((\sin(ax^2+bx))^\prime = (2ax+b)\cos(ax^2+bx)\)
例 2
\((\sin^3 x)^\prime = 3\sin^2 x \cos x\)